Sosialisasi Pemilihan Alat Kontrasepsi Pada Wanita Usia Subur Di Desa Budong – Budong - Parwati, Dewi; Thalib, Kiki Uniatri; Susanti, Susanti; D, Yuliana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The government's efforts to achieve the third SDGs goal by implementing the Family Planning program are implemented as a means to suppress population growth and improve maternal and child health in the context of high maternal mortality rates, and provide access to contraception for couples of childbearing age or older women. Contraception is a method or method that aims to prevent pregnancy. The design of the mechanism for implementing this activity refers to the four steps of action research, namely: planning, action, observation and evaluation and reflection on activities. The implementation of this activity takes the form of implementing a community service program which is carried out in the form of a pre-test and post-test regarding women's understanding of contraceptive methods, providing counseling on contraceptive selection, health checks and providing leaflet facilities. Based on the results, it shows that the majority of respondents are classified as having good knowledge. This is natural because the majority of respondents already have sources of information with this sophisticated ssat technology.